The rebound effect and the challenge of moving beyond fossil fuels: A review of empirical and theoretical research. (9th May 2022) - York, Richard; Adua, Lazarus; Clark, Brett
Abstract: William Stanley Jevons identified what has come to be known as the Jevons paradox: the observation that improvements in energy efficiency are often connected with rising, not falling, energy consumption. This insight informs the subsequent economic concept of the "rebound effect" and the expansive research investigating this relationship. We provide an overview of key empirical research, which establishes that large rebounds in energy consumption connected with rising energy efficiency are common across various units of analysis, including the national, subnational (e.g., states/provinces/cities; power plants), and household levels. We then focus on the range of theoretical arguments that have been put forward to explain why rebounds occur in varying contexts, with particular consideration of implications for efforts to move away from fossil fuels. We emphasize the important distinction between direct effects, indirect effects, and economy‐wide effects in regard to rebounds, particularly those connected with macro‐structural forces, for understanding the causes and implications of the Jevons paradox. This article is categorized under: The Carbon Economy and Climate Mitigation > Decarbonizing Energy and/or Reducing Demand Abstract : The Jevons Paradox. Each circle represents a steam engine, and the area of the circle represents the amount of coal it consunmes. At time 1, each engine consumes a lot of coal, but there are not many of them. At time 2, the engines are more efficient, consuming less coal each, but there are many of them.